MiceKings : The Helmet Holdup - Stilton, Geronimo (United States Scholastic Inc., 2017)
n The Helmet Holdup (Micekings #6) by Geronimo Stilton, Geronimo Stiltonord and the Micekings travel to the rival Vilekings' village after a special helmet is stolen from Sven the Shouter. They must navigate dangerous dragons, forge an unlikely alliance with their rivals to survive, and recover the stolen artifact.
English
Keywords: Juvenile fiction; action-adventure; humor